2013
DOI: 10.1007/s00394-013-0492-z
|View full text |Cite
|
Sign up to set email alerts
|

Yeast (1,3)-(1,6)-beta-glucan helps to maintain the body’s defence against pathogens: a double-blind, randomized, placebo-controlled, multicentric study in healthy subjects

Abstract: PurposeThe effect of brewers’ yeast (1,3)-(1,6)-beta-d-glucan consumption on the number of common cold episodes in healthy subject was investigated.MethodsIn a placebo-controlled, double-blind, randomized, multicentric clinical trial, 162 healthy participants with recurring infections received 900 mg of either placebo (n = 81) or an insoluble yeast (1,3)-(1,6)-beta-d-glucan preparation (n = 81) per day over a course of 16 weeks. Subjects were instructed to document each occurring common cold episode in a diary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 18 publications
4
50
0
1
Order By: Relevance
“…In other countries, glucan is still only a supplement. However, more and more studies are now focused on the use of glucan in clinical practice, including numerous clinical trials (Bergendiova et al, 2011;Lehne et al, 2005;Auinger et al, 2013;Jesenak et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…In other countries, glucan is still only a supplement. However, more and more studies are now focused on the use of glucan in clinical practice, including numerous clinical trials (Bergendiova et al, 2011;Lehne et al, 2005;Auinger et al, 2013;Jesenak et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…18 Consumption of yeast b-glucan has been associated with fewer symptoms of acute respiratory infection (ARI) in healthy adults. [19][20][21] A b-glucan from a different fungal source was reported to promote an increase of blood NK lymphocytes and fewer ARIs in children with recurrent ARIs. 22 However, no data on immune benefits of dietary intake of yeast b-glucan in children is currently available.…”
mentioning
confidence: 99%
“…In this context, special foods enriched with molecules with health benefits are been developed. Some studies dealing with the enormous benefits of β-glucan as a nutritional supplement [31,[35][36][37]. Used as adjunctive to the positive effects of antioxidants, lipid balance enhancers, antibiotics, and other therapeutics, the β-glucans are currently considered a true antiaging supplement.…”
Section: Food and Feed Applications Of β-Glucansmentioning
confidence: 99%
“…A study with seventy-five marathon runners showed that daily administration of β-glucan can prevent upper respiratory tract (URTI) symptoms and improve overall health and mood following a competitive marathon [36]. More recently, a study of 162 healthy participants with recurring infections who received a diet supplemented with β- (1-3), (1)(2)(3)(4)(5)(6) glucan showed a reduction in the number of symptomatic common cold infections by 25% and the mean symptom score was 15% lower compared to the control group [35].…”
Section: β-Glucan In the Human Dietmentioning
confidence: 99%